Application of Artificial Intelligence on Library System, Operations and Services (LIS TODAY, 2022)
This paper is going to aware in the field of Artificial Intelligence focusing on how it’s applied in the Library  world. The concept such as machine learning, deep learning and their various applications by Technique is  enumerated. In this paper an attempt has been made to identify the different applications of Artificial  Intelligence into the libraries. The various concepts such as expert system, natural language processing, pattern  recognition and robotics and their application to the library operation and services have been explained  thoroughly. The advantages and disadvantages of Artificial Intelligence have also been discussed.
Keywords: Consciousness; artificial intelligence; machine learning; deep learning; expert system; natural language processing; pattern recognition and robotics